Pemenuhan Hak Kesehatan Reproduksi dan Seksual dalam Kerapuhan Sistem Pangan Komunitas di Perdesaan Indonesia - Widya Hasian Situmeang; Fairuz Rafidah Aflaha; Wahyu Ridwan Nanta (Jurnal Perempuan, 2023)
Women’s authority over their bodies is often ignored due to limited choices and access to resources. This study intends to photograph the failure of development governance, especially in the food and environmental sectors, which places women as the exploited party. This research uses the concept of feminist ecology as a rationale in studying women’s experiences and their relation to the fragility of the food system. The research method used in this research is a qualitative approach through in-depth interviews and observations in the area of Kampung Darim which is uniquely divided into the territories of Kendayakan Village and Puntang Village with a food-agricultural ecosystem background in Indramayu Regency, West Java. These two villages are one of the food barn areas and have a high tendency for the practice of early marriage to occur. The results of the study show that the commodification of natural resources, especially food, tends to reduce the function of food production to fulfilling daily needs. More than that, it also ignores cultural practices that are closely tied to the food system. This paper intends to raise the experience of women who are vulnerable to exploitation due to the failure of the food system. Apart from experiencing exploitation as a result of failure to manage natural resources, rural women in this study are also a group at high risk of experiencing sexual and reproductive health threats. The development of the food system needs to be improved by placing women as equal subjects